Retention of zirconia crown to oxidized titanium base abutment: Experimental research. - Rawikorn Krongvanitchayakul; Chatchai Kunavisarut (PLoS ONE, 2023)
Statement of problem To separate the crown from the titanium base abutment, by using heat, caused oxidization of the titanium base abutment. The effect of this procedure on the retention of a crown is unclear. Purpose To compare the resin bond strength and failure type between zirconia crowns and titanium base abutments utilizing four different surface treatments. Surface roughness and morphology of each surface treatment were also investigated. Material and methods Forty titanium base abutments (Variobase®) were divided into four groups, 1. Control, 2. Air abraded, 3. Oxidized, and 4. Oxidized-air abraded. Oxidized and oxidized-air abraded groups were debonded from zirconia crowns using constant dry heat at 500 ˚C. For air abraded and oxidized-air abraded groups (after oxidization), the titanium base abutments were air abraded with Al3O2. After cleaning, one specimen of each group was investigated under a non-contact profilometer (50x), then the same samples were investigated under SEM at 25,300,500,1000 magnification and EDS at 30kV of accelerated voltage. All specimens were then cemented (RelyX Ultimate). After aging, with thermocycling under 5C° to 55C°,120 seconds dwell time for 5,000 cycles, bond strength was tested and statistical differences were calculated with One-way ANOVA (p-value <0.05) follow by Tukey test. All separated crowns and titanium base abutments were investigated under a light microscope (20x), using fisher's exact test for correlation of the failure types. Results There was a significant difference in the mean value of tensile bond strength among the control and test groups. Comparisons between control(237.6±46.3N) and oxidized(241.7±46.3N) showed statistically different values from air abraded(372.9±113.2N) when assembled using different surface treatments of the titanium-based abutments. (p-value<0.005) As for failure type, there were statistically significant differences between control versus air abraded, control versus oxidized-air abraded, oxidized versus air abraded, and oxidized versus oxidized-air abraded. (p-value<0.001) The titanium surface morphology shown from the profilometer and SEM was coordinated. Control (Ra 333.8nm) and oxidized (Ra 321.0nm) groups surfaces showed smooth, corrugated surfaces, meanwhile air abraded (Ra 476.0nm) and oxidized-air abraded (Ra 423.8nm) groups showed rough, rugged surfaces. Conclusion Heat oxidization of titanium-based abutments did not adversely affect tensile bond strength or the failure mode and surface roughness between titanium base abutments and zirconia crowns. However, air abrasion of the titanium surface increased surface roughness and retentive strength. Clinical implications The titanium base abutments that were oxidized under heat treatment did not have an effect on crown retention. Thoroughly air abraded the titanium abutment prior to cementation can increase cement bond strength.